Therapeutic plasma exchange in amatoxin associated acute liver failure-results from the multi-center Amanita-PEX study - Stahl, Klaus; Nalbant, Bahar; Pape, Thorben; Breteau, Isaure; Coirier, Valentin; Cardoso, Filipe S.; de Haan, Jubi; Janik, Maciej K.; Wasmuth, Jan-Christian; Madaleno, João; Merle, Uta; Frohme, Josephine; et al. (Critical care, 2025)
Background: Amatoxin-related acute liver failure (AT-ALF) carries high mortality without liver transplantation (LTX). While therapeutic plasma exchange (PEX) might improve LTX-free survival in other ALF cases, its role in AT-ALF is unclear. Clinical practice varies, and, given the rarity of this ALF entity, the feasibility of conducting a randomized controlled trial to investigate PEX in AT-ALF is more or less impossible. Methods: The Amanita-PEX study is a multi-center, international, retrospective study analyzing patients with AT-ALF from 2013 to 2024. The primary outcome was 28-day LTX-free survival (composite endpoint: death or LTX) after ALF diagnosis. Results: The study included 111 patients from 25 centers: 82 received standard-of-care (SOC), and 29 received at least one PEX-session. PEX and SOC-groups were comparable at baseline, but 76% of PEX- vs. 58% of SOC-patients developed hepatic-encephalopathy (HE) grade ≥ 2 (p = 0.021). While the primary outcome of 28-day LTX-free survival in all patients was not different between the SOC and PEX-groups, in the subgroup of patients with maximal HE grade ≥ 2, LTX-free survival was 19.1% (n = 8/42) in the SOC group, while it was 36.4% (n = 8/22) in patients receiving adjunctive PEX (Gehan-Breslow-Wilcoxon-p = 0.041, Log-Rank-p = 0.060). PEX was independently associated with reduced risk of the combined endpoint death or liver transplantation within 28 days from inclusion in patients with HE grade ≥ 2 (HR 0.37, 95%-CI 0.19–0.73, p = 0.004). After propensity-score-matching, LTX-free survival was 28% in the SOC- and 52% in the PEX group (Gehan-Breslow-p = 0.036; Log-Rank-p = 0.035). Conclusions: In this real-world study, adjunctive use of PEX was associated with increased LTX-free-survival in patients with AT-ALF and HE grade ≥ 2.
Veröffentlicht: 30. Oktober 2025
Gesehen am 02.01.2026